Safety of hormonal treatments in women with genitourinary syndrome of menopause and a history of breast cancer: systematic review and meta-analysis (Revista Científica Integrada, 2025)
Objective: To analyze the use of hormonal therapy in women with genitourinary syndrome of menopause (GSM) and a history of breast cancer. Methods: This is a systematic review conducted in April 2025, including observational studies and clinical trials published between 2019 and 2024 in the PubMed, Scopus, SciELO, and BVS databases. Studies investigating postmenopausal women diagnosed with GSM, with a history of breast cancer and using hormonal therapy, were included. A meta-analysis was performed using a random-effects model, considering hazard ratios (HR) and their respective confidence intervals. Results: Of the 105 studies identified, 10 met the eligibility criteria, totaling 142,717 women. The most frequent intervention was the use of vaginal estrogen. The meta-analysis revealed a pooled HR of 0.95 (95% CI: 0.87–1.03), suggesting no significant risk for recurrence or mortality. Studies also reported improvement in GSM symptoms without elevation in serum estradiol levels. Conclusion: Evidence suggests that the use of vaginal estrogen in women with GSM and a history of breast cancer is safe when carefully indicated. Clinical decisions should consider the individual profile of each patient, promoting evidence-based interventions that enhance quality of life.
Keywords: Genitourinary Syndrome of Menopause; Breast Cancer; Estrogen therapy